MEMPERSIAPKAN LAPORAN KEUANGAN DAN ADMINISTRASI USAHA UNTUK MEMENUHI PERSYARATAN PENGAJUAN KREDIT OLEH UMKM DI KELURAHAN MERUYA UTARA - M, HIRDINIS; Yuhasril, Yuhasril; Haningsih, Luna (FKIP Universitas Wisnuwardhana, 2024)
Common problems with micro, small, and medium enterprises (MSMEs) in the community are the lack of ability of MSME actors to increase income and a lack of knowledge about how to obtain additional capital through bank credit or from investors. MSMEs in the North Meruya sub-district face difficulties obtaining additional capital to sustain their businesses. The Mercu Buana University (UMB) Community Service Team (PkM) wants to help MSMEs in North Meruya District by providing guidance and assistance in making financial and administrative reports, which are a requirement for applying for banking credit. Implementation of PkM activities revealed that the participating MSME business owners had not used credit facilities from the government and banks to achieve business sustainability. MSME players also have not prepared financial reports that comply with accounting standards and have not prepared complete documents for the requirements for applying for banking credit. Apart from that, related parties, banking institutions, and the government have not been able to share information regarding banking credit that should be conveyed to MSME players. For this reason, cooperation between banking institutions, the government, and the community needs to be improved so that MSME players have information about credit requirements and application procedures.